Facilitating the Teaching of Arabic to Non-Native Speakers Using Computers: A Computational Linguistic Study - Ahamed Zubair K M A (Jurnal Bahasa Arab, 2025)
This study examines the impact of computational linguistics on the acquisition of Arabic language skills by non-native speakers. The research focuses on the use of computer-assisted language learning (CALL) tools and their effectiveness in enhancing students' proficiency in grammar, vocabulary, and pronunciation. An experimental design was employed, with participants divided into two groups: one utilizing CALL tools and the other following traditional teaching methods. The findings reveal that students using CALL tools showed significant improvements in language skills, higher engagement, and increased motivation compared to those taught using conventional methods. Statistical analysis confirmed the effectiveness of CALL tools, demonstrating a significant difference in learning outcomes between the groups. The study also identifies challenges, such as technical issues and cultural sensitivity, and recommends integrating artificial intelligence for personalization and incorporating cultural contexts into future developments.